PERANAN INSPEKTUR ANGKUTAN UDARA OTORITAS BANDAR UDARA WILAYAH III TERHADAP IMPLEMENTASI STANDAR PELAYANAN PENUMPANG MASKAPAI SRIWIJAYA AIR DI BANDAR UDARA INTERNASIONAL JUANDA SURABAYA - Jumlad, Walid; Renita Prahenmutia, Risma (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
Supervision of minimum passenger service standards carried out by air transport inspectors aims to ensure safety and adequate service in the aviation industry in accordance with Ministerial Regulation (PM) Number 30 of 2021 which regulates minimum service standards for air transport passengers. Monitoring minimum service standards by air transport inspectors is part of efforts to ensure that airlines comply with the requirements set out in regulations. This research was conducted from January to April 2024. This research is a qualitative descriptive research. The data analysis technique method can be carried out in four stages, namely data collection, data reduction, data presentation, and drawing conclusions. Data collection is reviewed directly through interviews, observations, and documentation at the Surabaya Region III Airport Authority. This research provides results on the role of Air Transport Inspectors in implementing supervision of minimum service standards for air transport passengers at Juanda International Airport, Surabaya. Air transport inspectors carry out scheduled supervision planned in the work program to ensure the implementation of airline compliance in implementing aviation regulations. The obstacle faced is the inability to carry out continuous monitoring, especially when there is no physical presence at the airport. A mechanism is needed to monitor operations regularly and efficiently. The suitability of airline SOPs to field conditions at the airport also needs to be considered so that operations run efficiently. Good coordination between airlines and increased communication are needed to overcome the impact of these changes.